2019
DOI: 10.1002/lary.28191
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery in head and neck surgery: Reduced opioid use and length of stay

Abstract: Objectives: Enhanced recovery after surgery (ERAS) protocols were first developed in colorectal surgery and sought to standardize patient care. There have been several studies in the head and neck surgical literature looking at outcomes after ERAS protocol, but no studies focusing on narcotic use and length of stay. This study aimed to evaluate narcotic usage and length of stay, in addition to several other outcomes, following the implementation of an ERAS protocol.Methods: A head and neck-specific ERAS protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 34 publications
3
84
0
Order By: Relevance
“…Additional study will be necessary to titrate opioid prescriptions to pain management goals in the context of aggressive multimodal opioid‐sparing analgesia for this population. Although several groups have already explored this concept, future pain management algorithms may be improved by giving more OME to patients at higher risk to experience pain based on the risk factors identified in our study and less OME for those at lower risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional study will be necessary to titrate opioid prescriptions to pain management goals in the context of aggressive multimodal opioid‐sparing analgesia for this population. Although several groups have already explored this concept, future pain management algorithms may be improved by giving more OME to patients at higher risk to experience pain based on the risk factors identified in our study and less OME for those at lower risk.…”
Section: Discussionmentioning
confidence: 99%
“…The high rates of long‐term opioid use among head and neck cancer patients underscore the vulnerability of this population to opioid dependence and the importance of thoughtful pain management by the head and neck surgical team. Indeed, several recent studies have reported successful opioid prescription reduction without compromising pain control by implementing multimodal analgesia regimens for head and neck surgery patients …”
Section: Introductionmentioning
confidence: 99%
“…Appropriate study sample size was determined to provide 80% power at a two‐sided t ‐test with a significance level of .05. An assumption of an effect size of an individual outcome was based on two available directly comparable studies 12,13 . A group assignment ratio of 1:2 was chosen to reach power.…”
Section: Methodsmentioning
confidence: 99%
“…Though ERAS theory has become widely accepted and gradually extended to elective surgical treatments, there are only a few reports concerning the application of ERAS theory around head and neck cancer in the field of otolaryngology, head and neck surgery, probably due to the particular clinical symptoms of the diseases encountered in that therapeutic area. [3][4][5] Obstructive sleep apnoea (OSA) in children is characterised by the recurrent upper airway obstructive events that occur during sleep, and can eventually influence child's physical and mental growth. Hypertrophy of the adenoids and tonsils is a main cause of OSA in children, and adenotonsillectomy may decrease the adverse effects of OSA.…”
Section: Introductionmentioning
confidence: 99%